Preparation and Characterization of tetra dentate Schiff- base ligand with some its complexes derived from thiosemicarbazone and Î²-[P-(2-pyrimidyl Sulhamyl) phenyl azo)] Ketonilide (SDPA) - Layla. Ali. Mohammad (Al-Qadisiyah Journal of Pure Science, 2017)
Anew series of transition metal complexes of Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Hg(II) have been preparation and characterization using anew Schiff base (SDPAT) derived from anew azo dye were Î² [-(2-Pyrimidyl Sulphamyl) phenylazo)] ketoanilid and thiosemicarbazide were characterized by several techniques, including elemental analysis (C.H.N), molar conductance, magnetic measurements, electronic spectral, IR spectral studies and 1HNMR. The data show that these complexes have composition of [ML]X2 type. The electronic spectral, and magnetic susceptibility data of the complexes suggest square planar geometry of all complexes, and the ligand (SDPAT) behaves natural and tetra dentate manner, by coordination through the azomethane nitrogen atoms and sulffer groups of the thiosemicarbazide.